The presence of the undertaken social and economic role in the university’s strategy-making - Németh, Szabolcs (Acta Agraria Debreceniensis, 2012)
It is vital to examine the strategic plans and leadership insights of the university, the faculties, the departments and the institutions in the research of the „third mission” of the universities. Because of the undertaken social-economic role in the region it is indispensable to know the turbulently changing environment (hazards – opportunities), to map the competencies available in the university (strengths – weaknesses) and to recognize the relations between the external and internal environment. It is an important factor to define the strategic directions of the departments, examining them in direction dimension (pro-active – adaptive) and in role dimension (top-down – bottom-up). The main objective of this research is to recognize the formal and informal strategic visions of the institutes and departments in the Centre for Agricultural and Applied Economic Sciences of the University of Debrecen, and to examine how these visions are related to the university’s role in the regional innovation system.